SYNERGETIC APPROACH TO THE CALCULATION OF ONE-GROUP TRAIN FORMATION PLAN - Negrey, V. Y.; Shkuryn, K. M. (Science and Transport Progress, 2018)
Purpose. The research aims at the analysis of the possibility of using in the development of one-group train formation plan the criterion, which allows to consider the costs associated with the movement of cars and locomotives. Methodology. The existing methods for development of train formation plan and current directions of its optimization are analyzed. The formulas for calculating the cost-saving criterion for running cars and locomotives in through-trains have been developed. Findings. The dependence between the service speed and the category of train was analyzed on the examples of railway sections of the Belarusian Railways. The obtained results allowed to conclude that, in general, the service speed of through-trains is higher than that of local trains. At the same time, the traffic intensity and section capacity affect the difference between the service speeds of trains belonging to the different categories. The one-group train formation plan was developed using the traditional methods and the proposed criterion on the example of the railway direction, where four marshalling yards are located. The use of the proposed methodology for the development of train formation plan can provide significant savings in operating costs due to the acceleration of the passing of the car through the railway sections. Originality. The use of the additional parameter in the development of train formation plan – «the criterion of cost saving when running of rolling stock in through-trains» – is proposed. It is shown that the application of this criterion makes it possible to substantiate the creation of separate assignments of some car-streams, while these car-streams would be considered as unprofitable, when using traditional methods of the calculation of train formation plan. The authors analyzed the influence of such factors as the train composition, the length of the railway section and the car traffic volume on the cost savings by using the proposed criterion. Practical value. The obtained results can be used in the development of the train formation plan, which will save the operating costs connected with the movement of cars and locomotives.